A leitura e a formação do leitor no 1º e 2º ciclos de aprendizagem - Silva, Joana Dar'c Vitória da (2010)
Each day is demanded that the readers are proficient and present language domain abilities to make possible the full social participation and the school has the attribution of forming readers. Considering the difficulties presented by that Brazilian students had in reading and understanding in all education levels, the interest of this research appeared. In that sense, this dissertation aims to analyze what form has been worked the reading at school, for the teachers in the first and the second cycles final years of learning under the proficient readers' perspective formation. Then the theoretical language sciences contribution was used, the psycholinguistic and more specifically of the textual linguistics, that it proposes the investigation of the constitution, of the operation, of the production and of the understanding of the texts in use. It was characterized as a qualitative research, based on documental analysis, observation of the classes of six subject with registrations in the field diary and interview narrative. The analysis of the data indicated there to be different theoretical-methodological perspectives regarding the reading work and readers' formation. In one of them work him/it of readers' formation privileges the reading as decoding. In the other perspective, the reading is observed as a process of construction of senses, favoring the proficient reader's formation Those data appear for the need of a larger investment in the public net, with focus in the teachers' preparation to form critical readers. They also appear for the socialization in net of the significant experiences in the sense of the accomplishment of a work of proficient readers formation.